Outcomes of double-balloon enteroscopy-assisted direct percutaneous endoscopic jejunostomy tube placement - Al-Bawardy, Badr; Gorospe, Emmanuel C.; Alexander, Jeffrey A.; Bruining, David H.; Coelho-Prabhu, Nayantara; Rajan, Elizabeth; Wong Kee Song, Louis M. (Endoscopy, 2016)
Background and study aims: In a large series, conventional direct percutaneous endoscopic jejunostomy (DPEJ) tube placement with push endoscopes failed in approximately one-third of patients. In a pilot study, double-balloon enteroscopy (DBE)-assisted DPEJ tube placement was successful in all patients in whom attempted conventional DPEJ had failed. The study aim was to assess the technical success of and adverse events related to DBE-DPEJ tube placement in a large cohort of patients.Patients and methods: The medical records of all patients who underwent DBE-DPEJ tube placement between July 2010 and November 2013 were reviewed using a prospectively maintained electronic database. Data were abstracted for patient demographics, indications for DPEJ, gut anatomy, technical success rate, causes of failure, and adverse events.Results: The study comprised a total of 94 patients (39 men; mean age 56 years; body mass index [BMI] 23 ± 6.4 kg/m2). The most common indication for DPEJ was gastroparesis (n = 29). Altered gut anatomy was present in 36 patients (38 %). DBE-DPEJ tube placement was technically successful in 87 patients (93 %). The mean procedure duration was 33 minutes (range 15 – 88). DBE-DPEJ tube placement failed in seven patients (7 %), primarily because of limited instrument advancement in the setting of presumed surgical adhesions. Post-procedural adverse events occurred in eight patients (9 %), with one serious adverse event, which was a gastric interposition requiring surgical repair. Conclusions: Compared with the published outcomes of DPEJ by conventional endoscopy, DBE-DPEJ tube placement was technically successful in a high proportion of patients (93 %) and with a relatively low rate of significant adverse events.